Arbitrating Intersection Crossing using V2I communications - Andréasson, Mathias; Hasselquist, Tomas (My University, 2018)
In the domain of automated driving, virtual traffic lights (VTLs) are key to making efficient intersection crossings. However, the design of an automated VTL remains an open challenge. This dissertation provides the design and implementation of a VTL prototype that can tolerate a multitude of failures, such as positioning system inaccuracy, packet omission and communication delays. As such, our fault tolerant VTL can be a critical building block for future automated driving systems, completing existing autonomous driving efforts. We also present a prototype implementation and evaluate the protocol through extensive simulations. From our evaluation we establish interesting trade-offs in the system design. One such trade-off is observed when stopping vehicles further from the intersection, this reduces the negative impact of positioning system inaccuracies. Another example is that raising the frequency of message transmissions both improves recovery time of the system as well as acting as an effective remedy for severe packet omissions.
Keywords: Data- och informationsvetenskap; Computer and Information Science